This thread is only Q&A!

Given a Hilbert space $\mathcal{H}$.

Consider a spectral measure: $$E:\mathcal{B}(\mathbb{C})\to\mathcal{B}(\mathcal{H})$$

Regard the domain: $$\int|f(\lambda)|^2\mathrm{d}\|E(\lambda)\varphi\|^2<\infty$$

And the calculus: $$\langle f(E)\varphi,\chi\rangle=\int_\mathbb{C} f(\lambda)\mathrm{d}\langle E(\lambda)\varphi,\chi\rangle$$

Then equivalence holds: $$\mathcal{N}f(E)=(0)\iff E\{f=0\}=0$$

Especially one has: $$f(E)^{-1}=f^{-1}(E)$$

How to prove this?

up vote 0 down vote accepted

By the calculus: $$f(E)E\{f=0\}=(f1_{\{f=0\}})(E)=0$$

Thus one has: $$\varphi\in\mathcal{R}E\{f=0\}\implies f(E)\varphi=0$$

Conversely regard: $$f^{-1}(\lambda):=\frac{1}{f(\lambda)}\quad(E(\lambda)\neq0)$$

By the calculus: $$f^{-1}(E)f(E)\subseteq(f^{-1}f)(E)=1(E)=1$$

But the domains agree: $$\mathcal{D}f^{-1}(E)f(E)=\mathcal{D}(f^{-1}f)(E)\cap\mathcal{D}f(E)=\mathcal{H}\cap\mathcal{D}f(E)=\mathcal{D}f(E)$$

So for the operator: $$\varphi\in\mathcal{D}f(E):\quad f^{-1}(E)f(E)\varphi=\varphi$$

Hence one obtains: $$f(E)^{-1}\subseteq f^{-1}(E)=(f^{-1}(E)^{-1})^{-1}\subseteq f(E)^{-1}$$

Concluding the assertion.

Your Answer

 

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.